2000
DOI: 10.3109/02770900009087304
|View full text |Cite
|
Sign up to set email alerts
|

Value of Bronchial Challenge in Scuba Diving Candidates

Abstract: Bronchial challenges were effected with carbachol in 76 subjects who were candidates for a scuba diving group. Bronchial reactivity was assessed through airway resistance and forced expiratory volume in 1 sec (FEV1) measurements. Medical interrogation had revealed symptoms of recent (RA) or ancient (AA) asthma, or allergic rhinitis (AL). Nearly half of the subjects (47%) presented bronchial hyperresponsiveness (BHR), which was much more frequent in the RA group, but whose strength did not depend on clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In fact, there is one study that showed a significantly higher prevalence of airway hyperresponsiveness to histamine in military scuba divers when compared to non-diving control subjects, whereas divers and controls did not differ significantly with respect to atopy and smoking. [45] It is important to note that a shift from nose breathing to combined mouth and nasal breathing at ventilation levels exceeding 30 L/min may account for a greater deposition of inhaled particles to the lower airways, and inadequately conditioned air may reach the lower airways. [57] This mechanism may intensify the airways' response to dehydration injury in mouth breathing scuba divers when compared to other sports.…”
Section: Airway Hyperresponsiveness and Divingmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is one study that showed a significantly higher prevalence of airway hyperresponsiveness to histamine in military scuba divers when compared to non-diving control subjects, whereas divers and controls did not differ significantly with respect to atopy and smoking. [45] It is important to note that a shift from nose breathing to combined mouth and nasal breathing at ventilation levels exceeding 30 L/min may account for a greater deposition of inhaled particles to the lower airways, and inadequately conditioned air may reach the lower airways. [57] This mechanism may intensify the airways' response to dehydration injury in mouth breathing scuba divers when compared to other sports.…”
Section: Airway Hyperresponsiveness and Divingmentioning
confidence: 99%
“…[5,8] A recent study which investigated 76 diving candidates with a history of recent or ancient asthma, or a history of allergic rhinitis, showed that nearly half of the subjects (47%) presented airway hyperresponsiveness to a carbachol challenge. [45] Only a few studies systematically investigated the association between airway hyperresponsiveness and diving. In a study of 28 consecutively recruited military scuba divers with a diving experience of at least 50 dives, 12 subjects (42.9%) significantly responded to a histamine challenge.…”
Section: Airway Hyperresponsiveness and Divingmentioning
confidence: 99%
“…In 30 subjects, the bronchial provocation test with hypertonic saline was positive (a fall in FEV1 of more than 15%) and they were excluded from diving. In subjects with a borderline post-saline fall in FEV1 (10-14.9%), the authors speculate that diving may be permissible if tests of static lung volumes and expiratory flows at low lung volumes derived from the flow-volume loop are normal [39]. The Thoracic Society of Australia and New Zealand [38] suggests that direct challenge tests are nonspecific and bronchial hyperresponsiveness to agents such as methacholine should not be considered an absolute contraindication for diving.…”
Section: Airway Hyperresponsiveness and Divingmentioning
confidence: 99%